Response assessment in myeloma: practical manual on consistent reporting in an era of dramatic therapeutic advances - Garderet, Laurent; Schönland, Stefan (Biology of blood and marrow transplantation, 2017)
The understanding and treatment of multiple myeloma (MM) have dramatically improved in recent years. However, accurate assessment of the response of myeloma to therapy and its subsequent relapse remains a difficult task. Criteria have changed over time and new parameters have recently been incorporated to evaluate minimal residual disease status. We present a practical approach to assess response and relapse/progression in myeloma in the context of its treatment. A robust reporting schema is crucial to correctly evaluate any treatment protocol and compare results across trials. MM is a highly heterogeneous disease with multifarious manifestations. To assess the tumor load decline after treatment and its increase during relapse/progression, numerous parameters need to be taken into account. As our ability and the tools to measure low levels of disease have improved over time, so have the accepted definitions of response, most recently in August 2016. The goal of this article is to define, describe, and clarify the practical methodological aspects of disease evaluation in response to therapy and in progression or relapse. We expect this practical manual will help myeloma professionals and research workers in data collection for registries and databases and clinical trial reporting.
Available online 8 March 2017
Gesehen am 21.06.2018